My Italian bulldozer - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Paul Stuart series., 2017)
"From one of our most beloved and best-selling authors: a hilarious new stand-alone novel about one man's misadventures in travel and romance in the Italian countryside. When writer Paul Stewart heads to the idyllic Italian town of Montalcino to finish his already overdue cookbook, he expects it to be the perfect escape from stressful city life. But when he arrives, things quickly take a turn for the worse. His hired car is nowhere to be found, and with no record of a reservation at the car-rental counter and no other cars are available, it appears that Paul will be stuck at the airport--that is, until an enterprising stranger offers him an unexpected alternative: a bulldozer. With little choice in the matter, Paul accepts, and so begins a series of laugh-out-loud adventures as he trundles through the Tuscan countryside. A story of unexpected circumstances and making the best of what you have, My Italian Bulldoze ris a warm and witty read guaranteed to put a smile on your face"--